Money Management System - Rahinj Dhanashri; Pawar Dnyaneshwari; Ghegade Vikram; Prof Shelke S.A; Dr. Divekar S. N. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Effective financial management is an important component for economic stability and growth, yet many individuals and small businesses lack the tools to monitor and optimize their finances systematically. This research focuses on the development of a "Money Management System" (MMS), a digital platform designed to address common financial management challenges through automated tracking and budget planning. The MMS offers features such as income and expense categorization, savings goals, and investment tracking, coupled with user friendly interface to enhance user engagement and comprehension of financial behaviors.
Keywords: Money Management; Financial Literacy; Income Tracking; Expense Tracking; Budgeting